An Integrative Multiomics Approach to Characterize Prebiotic Inulin Effects on Faecalibacterium prausnitzii - Park, Ji-Hyeon; Song, Won-Suk; Lee, Jeongchan; Jo, Sung-Hyun; Lee, Jae-Seung; Jeon, Hyo-Jin; Kwon, Ji-Eun; Kim, Ye-Rim; Baek, Ji-Hyun; Kim, Min-Gyu; Yang, Yung-Hun; Kim, Byung-Gee; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Faecalibacterium prausnitzii, a major commensal bacterium in the human gut, is well known for its anti-inflammatory effects, which improve host intestinal health. Although several studies have reported that inulin, a well-known prebiotic, increases the abundance of F. prausnitzii in the intestine, the mechanism underlying this effect remains unclear. In this study, we applied liquid chromatography tandem mass spectrometry (LC-MS/MS)-based multiomics approaches to identify biological and enzymatic mechanisms of F. prausnitzii involved in the selective digestion of inulin. First, to determine the preference for dietary carbohydrates, we compared the growth of F. prausnitzii in several carbon sources and observed selective growth in inulin. In addition, an LC-MS/MS-based intracellular proteomic and metabolic profiling was performed to determine the quantitative changes in specific proteins and metabolites of F. prausnitzii when grown on inulin. Interestingly, proteomic analysis revealed that the putative proteins involved in inulin-type fructan utilization by F. prausnitzii, particularly β-fructosidase and amylosucrase were upregulated in the presence of inulin. To investigate the function of these proteins, we overexpressed bfrA and ams, genes encoding β-fructosidase and amylosucrase, respectively, in Escherichia coli, and observed their ability to degrade fructan. In addition, the enzyme activity assay demonstrated that intracellular fructan hydrolases degrade the inulin-type fructans taken up by fructan ATP-binding cassette transporters. Furthermore, we showed that the fructose uptake activity of F. prausnitzii was enhanced by the fructose phosphotransferase system transporter when inulin was used as a carbon source. Intracellular metabolomic analysis indicated that F. prausnitzii could use fructose, the product of inulin-type fructan degradation, as an energy source for inulin utilization. Taken together, this study provided molecular insights regarding the metabolism of F. prauznitzii for inulin, which stimulates the growth and activity of the beneficial bacterium in the intestine.